Examining the interplay between HPV knowledge and participants' propensity for vaccination - Violeta Getova-Kolarova; Albena Zlatareva; Ivo Kumanov (Pensoft Publishers, 2024)
This is a national, qualitative and quantitative investigation involving 600 participants which employed interviews and standardized self-administered questionnaires to assess participants' HPV vaccine knowledge and their inclination to vaccinate. The results of the study underscore the pivotal influence of informed awareness campaigns in shaping vaccination behaviours and stress the imperative of tailored educational strategies to augment vaccine uptake. All respondents shared as a main concern insufficient information about the vaccine and low degree of familiarity. An inquiry into the correlation between having children and HPV vaccine knowledge revealed that individuals with children under 16 years old manifested heightened levels of HPV vaccine knowledge. The outcomes suggest that individuals with young children are more inclined to harbour comprehensive HPV vaccine knowledge.